Pre-sowing Treatment of Puna (Ehretia acuminata) Seed - Agarwal, S. S. (Indian Forester, 1986)
A study on pre-sowing treatment of Puna seed was carried out to find out the best m ethod of seed treatment. It was found that the seeds treated with Conc-sulphuric acid for 10 minutes and subsequently washed with water gave 87.6% germination. This is the maximum germination in comparison to other treatments.